2021
DOI: 10.3390/jpm11060582
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Birth Weight Improve Polygenic Risk Score for Type 2 Diabetes

Abstract: One of the major challenges in the post-genomic era is elucidating the genetic basis of human diseases. In recent years, studies have shown that polygenic risk scores (PRS), based on aggregated information from millions of variants across the human genome, can estimate individual risk for common diseases. In practice, the current medical practice still predominantly relies on physiological and clinical indicators to assess personal disease risk. For example, caregivers mark individuals with high body mass inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…In our machine learning framework, the variants slightly contributed to the discriminatory value ( Figure 5 B). It emphasized the benefit of including not only genetic signals, but also orthogonal medical and environmental data into a single model, as exemplified for Type 2 diabetes (T2D) [ 59 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In our machine learning framework, the variants slightly contributed to the discriminatory value ( Figure 5 B). It emphasized the benefit of including not only genetic signals, but also orthogonal medical and environmental data into a single model, as exemplified for Type 2 diabetes (T2D) [ 59 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Other, non-genetic risk factors, such as age, sex, smoking status, parental disease status, physical activity and body mass index (BMI), which already form part of most clinical risk prediction models, have proven more effective at identifying individuals at high risk [19][20][21] . Therefore, combining both genetic and non-genetic factors should lead to improved risk prediction, as previously suggested in a study that showed a T2D prediction model including BMI and PGS outperforms models including only either one of these predictors 22 . Furthermore, additional inclusion of a number of biomarkers further increased its discriminative power 23,24 .…”
Section: Genetic Health Risk Limitationsmentioning
confidence: 85%
“…In our machine learning framework, the variants slightly contributed to the discriminatory value (Figure 6B ). It emphasizes the benefit of including genetic variants with orthogonal medical and environmental data into a single model, as exemplified for Type 2 diabetes (T2D) [53]).…”
Section: Discussionmentioning
confidence: 99%